The effect of organizational structure on absorptive capacity in single and dual learning modes - Murad Ali; Imran Ali; Khalid A. Al-Maimani; Kichan Park (Journal of Innovation & Knowledge (JIK), 2018)
Structural theories of absorptive capacity (ACAP) usually aim to specify organizational design characteristics that lead to a high level of ACAP. Drawing on the theories of organizational design and knowledge management, this paper reviews how organizational structure relates to ACAP in single and dual learning modes. This study analyzed the structure of the ACAP relationship in management and organization studies based on a literature review of ACAP research. This study contributes to the ACAP literature in five ways: (1) it investigates the role of ACAP as an independent variable; (2) it focuses on the behavioral domain of ACAP; (3) it relates structural variables to ACAP in single and dual learning modes; (4) it establishes a link between structural variables and ACAP using a two-stage model, comprising initiation and implementation stages; and (5) it predicts ACAP by identifying several testable propositions and deriving two predictive contingency models. Several propositions and two predictive contingency models are recommended as directions for future research and theory construction.
Keywords: L1; L2; M10; M19; 650; Organizational structure; Absorptive capacity; Single mode; Dual mode